2020
DOI: 10.1039/c9ra10719c
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric sensing of chlorpyrifos through negative feedback inhibition of the catalytic activity of silver phosphate oxygenase nanozymes

Abstract: Ag3PO4 oxygenase nanozymatic activity towards chlorpyrifos sensing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…A detection limit of 1.82 μM pyrophosphate was able to be achieved. Kushwaha et al [ 150 ] reported the oxidase-like activity of Ag 3 PO 4 nanoparticles for the colorimetric detection of chlorpyrifos using TMB as a substrate. Ag 3 PO 4 was able to oxidise chlorpyrifos to chlorpyrifos oxon and sulphide ions.…”
Section: Detection Of Pesticidesmentioning
confidence: 99%
“…A detection limit of 1.82 μM pyrophosphate was able to be achieved. Kushwaha et al [ 150 ] reported the oxidase-like activity of Ag 3 PO 4 nanoparticles for the colorimetric detection of chlorpyrifos using TMB as a substrate. Ag 3 PO 4 was able to oxidise chlorpyrifos to chlorpyrifos oxon and sulphide ions.…”
Section: Detection Of Pesticidesmentioning
confidence: 99%
“…For the assays based on nanozyme activity modulation, these nanozyme-only detection systems require that the target has unique structures and interactions with nanozymes [19,[96][97][98][99][100][101][102]. For instance, our group developed a bioenzyme-free colorimetric assay of malathion, where the oxidase-mimetic activity of Ag3PO4/UiO-66 could be in- Although the binary ChE-nanozyme assays have great potential for pesticide and related biomarker determination, they have some limits that will impede their commercial fabrication.…”
Section: Assays Based On Nanozyme Activity Modulationmentioning
confidence: 99%
“…However, despite the high sensitivity and field applicability of this electrochemical sensor, the sample preparation was complex. Therefore, to overcome this limitation, the colorimetric method [ 22 , 23 , 24 ] and SERS [ 22 , 25 , 26 , 27 , 28 , 29 , 30 ] techniques were adopted. The SERS-based detection techniques did not require a separate probe to capture targets that were easily detected with high sensitivity because the unique characteristics of CPF could be immediately confirmed in the spectrum.…”
Section: Introductionmentioning
confidence: 99%